Pendidikan Islam dan Pengembangan Masyarakat yang Berbasis Pada Nilai-Nilai Toleransi dan Cinta Kasih di Desa Kayu Kebek Kecamatan Tutur Kabupaten Pasuruan - Yumah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2025)
The article discusses the role of Islamic education in building and developing a harmonious society through the internalization of values of tolerance and compassion. The focus of the study is Kayu Kebek Village, Tutur Sub-district, Pasuruan Regncy. Islamic education functions not only as a means of transmitting religious knowledge but also as an instrument for shaping an inclusive, respectful, and civilized community. The values of tolerance and compassion are implemented through religious activities, learning in educational institutions, and social interactions within the community. The research employs a cqualitative approach using observation, interviews, and documentation techniques. The findings reveal that the application of tolerance and compassion in Islamic education strengthens social solidarity, fosters closer relationships among community members, and creates a peaceful and just social environment. These findings highlight the crucial role of Islamic education as an agent of social change oriented toward holistic community development